FORMULASI KEBIJAKAN BADAN USAHA MILIK DESA UNTUK PEMANFAATAN POTENSI DESA DI DESA BATUAH KECAMATAN LOA JANAN KABUPATEN KUTAI KARTANEGARA - Selviana, Selviana; Apriani, Fajar (GOVERNANCE: Jurnal Ilmiah Kajian Politik Lokal dan Pembangunan, 2025)
Village-Owned Enterprises are business entitles who entire or most of their capital is owned by the village, managed by the Village Government and the village community, and aims to improve the welfare of the village community through the management of village potentials and assets. Then the Village-Owned Enterprise has an important role in managing the economic potential of the village, both natural resources and human resources, for the benefit of the village. The purpose of this study is to describe and analyze the policy formulation of Village-Owned Enterprise for the utilization of village potentials in Batuah Village, as well as identifying inhibiting factors. This study uses a qualitative descriptive method with the focus of research on the stages of policy formulation of Village-Owned Enterprise which includes the formulation of the problem, the preparation of the policy agenda, alternative selection and policy determination, as well as its inhibiting factors. The data sources come from the primary data, such as the Head of the Batuah Village, the Head and the Secretary of Village-Owned Enterprise as the key informant, and Batuah community as informants. This research also uses secondary data from reports, archives/report documents sources from the Batuah Village-Owned Enterprise. Data collection was carried out using interviews techniques, observations, and documents study. Data analysis using an interactive model. The results of this study concluded that the formulation of the Village-Owned Enterprise policy for the utilization of village potentials in Batuah Village had been carried out by involving various stakeholders, such as Village Government, Manager of Village-Owned Enterprises, and village communities. But in the policy formulation until its implementation there are still inhibiting factors including the limitations of human resources management of the Village-Owned Enterprises and village officials, low innovations in program management. This study recommends that there needs to be efforts to increase the capacity of human resources to optimize community participation and the need for innovative strategies in managing village potential so that local economic development in Batuah Village can be carried out sustainably.